Brief Communication: Pattern of antiepileptic drug induced cell death in limbic regions of the neonatal rat brain - Forcelli, Patrick A. (2011)
Phenobarbital and phenytoin, two drugs commonly used for the treatment of neonatal seizures, have been well-documented to induce neuronal apoptosis throughout many regions of the developing rat brain. However, several limbic regions have not been included in previous analyses. Because drug-induced damage to limbic brain regions in infancy could contribute to emotional and psychiatric sequelae, it is critical to determine the extent to which these regions are vulnerable to developmental neurotoxicity. To evaluate the impact of AED exposure on limbic nuclei, we treated postnatal day 7 rat pups with phenobarbital, phenytoin, carbamazepine, or vehicle, and examined nucleus accumbens, septum, amygdala, piriform cortex and frontal cortex for cell death. Histological sections were processed using the TUNEL assay to label apoptotic cells. Nucleus accumbens displayed the highest level of baseline cell death (vehicle group), as well as the greatest net increase in cell death following phenobarbital or phenytoin. Phenobarbital exposure resulted in a significant increase in cell death in all brain regions, while phenytoin exposure increased cell death only in the nucleus accumbens. Carbamazepine was without effect on cell death in any brain region analyzed, suggesting that the neurotoxicity observed is not an inherent feature of AED action. Our findings demonstrate pronounced cell death in several important regions of the rat limbic system following neonatal administration of phenobarbital, the first-line treatment for neonatal seizures in humans. These findings raise the possibility that AED exposure in infancy may contribute to adverse neuropsychiatric outcomes later in life.